A method for producing hollow multi-shell materials of amorphous metal oxides and their applications

Through the second-stage enhanced adsorption method and heat treatment regulation, the problem of defect control of multi-layer hollow shell metal oxide materials is solved, and high-efficiency spectral absorption and water evaporation rate are achieved, which significantly improves the photothermal conversion efficiency and reaction stability.

JP7649871B2Active Publication Date: 2025-03-21INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023553742
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-04
Filing Date
2021-06-25
Publication Date
2025-03-21
Estimated Expiration
2041-06-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the defect content of multi-layer hollow shell metal oxides in manufacturing and application, which limits the improvement of its photothermal conversion performance.

Method used

By using the two-stage enhanced adsorption method, metal ions adsorption is performed on the carbon ball template to form a thin layer of metal oxide with a significant concentration gradient, and then the defect content and photothermal conversion performance are controlled by regulating the heat treatment conditions and the gas phase environment.

Benefits of technology

The high-efficiency spectral absorption and high-efficiency water evaporation rate of multi-layer hollow shell metal oxide materials in photothermal water evaporation applications are achieved, significantly improving the photothermal conversion efficiency and reaction stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649871000001
    Figure 0007649871000001
  • Figure 0007649871000002
    Figure 0007649871000002
  • Figure 0007649871000003
    Figure 0007649871000003
Patent Text Reader

Abstract

The present invention relates to the technical field of functional materials, in particular to a hollow multi-shell material of amorphous metal oxide and its preparation and application. The method includes the steps of: 1) heating a carbon source aqueous solution to obtain a carbon sphere template through filtration, washing and drying; 2) dispersing the carbon sphere template obtained in 1) in a first metal salt solution, adsorbing by heating and drying in an oven to obtain a first solid precursor; 3) dispersing the solid precursor obtained in 2) in a second metal salt solution, adsorbing and drying in an oven to obtain a second solid precursor; and 4) roasting the second solid precursor obtained in 3) to obtain a hollow multi-shell material of amorphous metal oxide. The present invention uses a two-step enhanced adsorption method to introduce defect-controllable doping energy levels into the metal oxide hollow spheres, thereby achieving efficient absorption of each wavelength range in the solar spectrum.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims priority based on Chinese Patent Application No. 202110241311.7, filed on March 4, 2021, the entire contents of which are incorporated herein by reference. The present invention relates to the technical field of functional materials, in particular to hollow multi-shell materials of amorphous metal oxides and their preparation methods and applications. [Background technology]

[0002] Solar energy, as a type of clean energy that can be used forever, has great potential for development, but due to its low energy density and unstable factors, it is necessary to design more effective photoconversion materials to achieve efficient acquisition and utilization of solar energy. The solar-powered photothermal interface water evaporation system is an efficient and convenient water purification technology that has emerged in recent years. It uses only sunlight to heat the photothermal material to near the boiling point of water, and then the water source is guided to the surface of the material to achieve the effects of purification and sterilization through surface evaporation and condensation water recovery. Compared with traditional bulk water heating, it has the following unique advantages: first, the surface heating system can reduce the volume of heat receiving, improve the heat transfer efficiency and reduce heat loss; and second, the energy consumed to produce steam per unit volume is significantly reduced. In addition, the solar-powered photothermal interface water evaporation system has the characteristics of low requirements for the quality of the water source, high photothermal conversion efficiency, fast water evaporation rate, significant sterilization and water purification effect, and easy-to-use device, and can be used for seawater desalination, conversion of sewage to drinking water, purification of bacteria-containing wastewater, and can also be used for the rapid self-production of drinking water in extremely harsh environments.

[0003] The multi-shell hollow micro / nanostructure has the characteristics of large specific surface area, small density, special internal cavity structure, and adjustable shell wall made of low-dimensional nanoparticles or nanorods, and thus can be widely used in many fields, such as sustained release of drugs, catalysis, sensors, water pollution control, nanoreactors and energy storage systems. When applied to the photothermal water evaporation field, the hollow multi-shell metal oxide material can scatter the incident light between the shells multiple times, effectively extending the light path and enhancing the light capture by the material, which contributes to efficiently absorbing solar light in the full spectrum and improving the photothermal conversion efficiency. In addition, the hollow multi-shell metal oxide material can provide a larger effective specific surface area, which contributes to the rapid transport and evaporation of water, and further improves the reaction efficiency.

[0004] At present, there are two main methods for producing multi-shell oxide hollow spheres: soft template method and hard template method. The soft template method means that micelles or emulsion droplets in a solution are used as templates, and a chemical reaction occurs at the interface between the two phases, and then the mixture is separated and dried to produce hollow microspheres. The currently reported soft template method is only applicable to the production of multi-shell hollow spheres of specific compounds, and the synthesized products have lower morphological uniformity, and it is necessary to use a large amount of organic solvent to produce reverse micelles or reverse microemulsions, which is not suitable for mass production and is difficult to be versatile. The hard template method means that monodisperse inorganic, polymeric or resin micro-nanoparticles are used as templates, and various chemical materials are deposited on the surface, and then the template is extracted by calcination or solvent extraction to form a uniform hollow sphere material. The core-shell material produced by the hard template method has the advantages of high monodispersity, high reproducibility and stable product morphology, and has attracted the attention of researchers.

[0005] CN102464304A discloses multi-shell metal oxide hollow spheres and a method for producing the same, which comprises preparing a carbon sphere template by a hydrothermal method, dissolving a metal salt in a carbon sphere suspension, and controlling the amount, depth and gradient distribution of the metal salt in the carbon spheres by adjusting the adsorption conditions such as the concentration of the metal salt, the pH value of the solution, the immersion temperature and time, and then heat-treating the carbon spheres adsorbing metal ions to obtain multi-shell metal oxide hollow spheres. The shell of the hollow spheres produced by this method is formed by depositing nanocrystalline grains of metal oxide, and the number of shells can be adjusted to 2 to 4 layers, and both the dimensions of the hollow spheres and the thickness of the shells can be controlled. The present invention has a simple method, is easy to carry out, has high controllability, is less polluting, is low cost and has versatility. The produced product has a hollow structure and a shell with a nanoscale thickness, and has a multi-layer structure, which allows the internal space to be effectively utilized, and is applied to gas detection and photocatalysis, and shows better performance than conventional nanomaterials and single-layer hollow spheres.

[0006] CN103247777A discloses a negative electrode material of tricobalt tetroxide multi-shell hollow spheres for lithium ion batteries and a method for preparing the same. Using carbon spheres prepared by hydrothermal method as a template, the ratio of water and ethanol in the cobalt salt solution, the temperature of the solution, and the adsorption capacity of the carbon spheres are controlled to control the number and depth of cobalt ions in the carbon spheres, thereby producing single-, double-, triple-, and quadruple-shell tricobalt tetroxide hollow spheres. However, the multi-shell hollow spheres prepared by this method are used to prepare negative electrode materials for lithium ion batteries, and their application in the photothermal field is still limited.

[0007] The above-mentioned manufacturing methods produce metal oxide crystals. There are no examples of research on the photothermal application of multi-shell hollow spheres, and photothermal research on semiconductors is limited to narrow band gap semiconductor nanoparticles such as copper oxide and copper sulfide, and nanowire arrays. Therefore, there are still few studies on the controllable synthesis of amorphous multi-shell hollow spheres with different defect contents, and the improvement of the photothermal properties of metal oxides by adjusting the defect content inside the amorphous, taking advantage of the depth of the nano-spatial scale of the multi-shell hollow spheres. Summary of the Invention [Problem to be solved by the invention]

[0008] Based on the above shortcomings, the present invention provides a preparation method and application of an amorphous metal oxide hollow multi-shell material, which makes the metal ions in the carbon sphere template have obvious concentration gradient after adsorption through two-stage enhanced adsorption, thereby obtaining an amorphous metal oxide hollow multi-shell material that can efficiently absorb the solar spectrum after roasting. [Means for solving the problem]

[0009] In order to achieve the above object, the present invention uses the following technical solutions.

[0010] The present invention provides a method for producing an amorphous metal oxide hollow multishell material, comprising: Step 1) The carbon source aqueous solution is put into a reactor and reacted by heating, and then filtered, washed and dried to obtain carbon sphere templates; Step 2) dispersing the carbon sphere template obtained in step 1 in a first metal salt solution, heating and adsorbing the metal salt, and drying the metal salt in an oven to obtain a first solid precursor; Step 3) dispersing the solid precursor obtained in step 2) again in a second metal salt solution, adsorbing and oven drying to obtain a second solid precursor; Step 4) roasting the second solid precursor obtained in step 3) to obtain an amorphous metal oxide hollow multi-shell material; The concentration of hydrated ions in the second metal salt solution is equal to or greater than the concentration of hydrated ions in the first metal salt solution.

[0011] In this method, the calcination temperature and the calcination atmosphere are the main factors in the synthesis of amorphous oxide and the adjustment of the defect content inside the amorphous. By selecting a metal oxide material with a high melting point, the diffusion transition energy of oxygen atoms in the metal oxide is low, and a network structure of oxygen atoms can be formed at low temperatures. Compared with oxygen atoms, the diffusion transition energy of these high melting metal ions is high, and the transition distance in a certain time is smaller than the size of one unit cell, then an amorphous oxide will be formed. Therefore, when the calcination temperature is controlled below the crystallization temperature of the metal oxide, that is, when the calcination heat does not reach the diffusion transition energy of metal ions, an amorphous oxide will be formed. The atmosphere (oxygen partial pressure) during calcination directly controls the defect content of the amorphous oxide, and the general rule is that the lower the oxygen partial pressure, the higher the defect content of the obtained amorphous oxide. The defect content of amorphous oxides is the main tuning method to obtain efficient light absorbing materials with wide absorption range and high absorption strength.

[0012] Meanwhile, the choice of solvent for adsorbing metal salt on carbon spheres is also very important, and different solvents are selected as precursor solutions, which will produce obvious differences in the adsorption depth of metal ions in the carbon sphere templates after adsorption. First, different solvents have different dissolving and dispersing abilities of metal salts, and there is a large difference in the aggregation size of metal cations in the solvent. In step (2), the metal salt solution with a relatively small ion aggregation radius can be deeply adsorbed inside the carbon spheres through dispersion and stirring adsorption operations, and in step (3), the metal salt solution with a relatively large ion aggregation radius is mainly aggregated on the surface of the carbon spheres through dispersion and adsorption operations, so that the solid obtained in step (3) has a larger metal adsorption amount and concentration gradient, and the metal oxide hollow spheres obtained after roasting have a larger number of shells. At the same time, when applied to the field of surface photothermal water evaporation, there are differences in the defect content of each layer in the amorphous multi-shell, and the light absorption efficiency of each layer can be superimposed, and a relatively closed spherical shape is formed inside the multi-shell. The light area limiting effect is significant, and an efficient light absorption effect is realized. Amorphous oxides, such as tantalum oxide, are indirect band gap semiconductors, which support the heat generation of phonons in the light-to-heat conversion process, i.e., heat transfer due to mutual vibration between unit cells. Secondly, the high content of defects improves the level of phonon scattering. Finally, it enhances the light-to-heat conversion efficiency.

[0013] The method of the present invention, in which the carbon-containing precursor aqueous solution is put into a reaction vessel for hydrothermal reaction, followed by cooling, filtering, washing and drying to obtain a carbon sphere template, has the following advantages: compared with the conventional mechanical milling method, the carbon spheres produced by the hydrothermal method have a uniform particle size, the size can be controlled, and they contain a large amount of active functional groups on the surface, have excellent hydrophilicity and surface reaction activity, and are conducive to the adsorption of metal ions; they are a commonly used template for producing core-shell structured materials.

[0014] The adsorption described in step 2) in the present invention is enhanced adsorption, which refers to a method in which the carbon sphere template and the metal salt solution are placed in a beaker and heated and adsorbed twice, in order to enhance the adsorption of metal ions by the carbon sphere template in the heated state, and then, after cooling, centrifuging, washing and drying, a solid precursor rich in metal salt ions is obtained.

[0015] Preferably, the carbon source in step 1) includes one or more of glucose, fructose, sucrose, maltose, starch and citric acid, more preferably sucrose.

[0016] The concentration of the carbon source in the aqueous carbon source solution is 0.1 to 6M, and may be, for example, 0.1M, 0.5M, 1M, 1.5M, 2M, 2.5M, 3M, 3.5M, 4M, 4.5M, 5M, 5.5M, or 6M, preferably 1 to 5M, and more preferably 2 to 3M.

[0017] Preferably, the heating reaction in step 1) is a hydrothermal reaction, and the temperature of the hydrothermal reaction is 175 to 220°C, for example, 175°C, 180°C, 185°C, 190°C, 195°C, or 200°C, more preferably 190 to 205°C, and even more preferably 195 to 200°C; The time for the hydrothermal reaction is 100 to 180 minutes, for example, 100 minutes, 110 minutes, 120 minutes, 130 minutes, 140 minutes, 150 minutes, 160 minutes, 170 minutes, or 180 minutes, more preferably 120 to 140 minutes, and even more preferably 125 to 135 minutes. The drying temperature is 60 to 100°C, and may be, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C, more preferably 70 to 90°C, and even more preferably 75 to 85°C. The drying time is 6 to 24 hours, for example, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, or 24 hours, more preferably 15 to 24 hours, and even more preferably 18 to 20 hours. The washing is performed using one or a combination of any two of deionized water, methanol, or ethanol, which may be, for example, deionized water, methanol, ethanol, a combination of deionized water and methanol, a combination of deionized water and ethanol, or a combination of methanol and ethanol.

[0018] The number of washing times is 2 to 5 times, and may be, for example, 2, 3, 4 or 5 times, and is preferably 3 to 4 times.

[0019] Preferably, the first metal salt solution and the second metal salt solution in step 2) and step 3) each include one or more of tantalum chloride solution, tantalum nitrate solution, tantalum sulfate solution, tantalum acetylacetonate solution, tantalum oxalate solution and tantalum ethoxide solution, more preferably, the metal salt solution selected in the present invention is a metal salt with a smaller hydrated ionic radius, which can enhance the adsorption depth of the metal in the carbon sphere and absorb the visible and infrared light portions of the solar spectrum multiple times.

[0020] The concentration of the first metal salt solution is 0.01 to 0.5M, and may be, for example, 0.01M, 0.1M, 0.15M, 0.2M, 0.25M, 0.3M, 0.35M, 0.4M, 0.45M, or 0.5M, more preferably 0.05 to 0.2M, and even more preferably 0.1 to 0.15M. The concentration of the second metal salt solution is 0.5 to 5M, for example, 1M, 1.5M, 2M, 2.5M, 3M, 3.5M, 4M, 4.5M or 5M, more preferably 1 to 3M, and even more preferably 1.5 to 2.5M. The solvent of the first metal salt solution includes one or more of water, acetone, and ethanol.

[0021] Preferably, the solvent of the first metal salt solution contains acetone and / or ethanol, and more preferably, the solvent of the first metal salt solution is ethanol; The solvent of the second metal salt solution comprises water, ethanol or a mixture thereof, and more preferably the solvent of the second metal salt solution is water.

[0022] Preferably, the adsorption in step 2) is a medium temperature stirring adsorption, The adsorption temperature is 20 to 60° C., and may be, for example, 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., or 60° C., more preferably 30 to 60° C., and even more preferably 40 to 50° C.; The adsorption time is 1 to 48 hours, more preferably 3 to 36 hours, and further preferably 6 to 24 hours. After the adsorption, the mixture obtained by the adsorption is centrifuged, and the solid in the lower layer is removed and washed with one or a combination of any two of deionized water, methanol, or ethanol, for example, deionized water, methanol, ethanol, a combination of deionized water and methanol, a combination of deionized water and ethanol, or a combination of methanol and ethanol.

[0023] The number of washing times is 2 to 5 times, for example, 2 times, 3 times, 4 times, or 5 times, and more preferably 3 to 4 times. The drying temperature is 60 to 100°C, and may be, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C, more preferably 70 to 90°C, and even more preferably 75 to 85°C. The drying time is 6 to 24 hours, and may be, for example, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours, more preferably 15 to 24 hours, and further preferably 18 to 20 hours.

[0024] The adsorption in step 3) is an intensified stirring adsorption by heating at medium temperature; The adsorption temperature is 20 to 60°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, or 60°C, more preferably 30 to 50°C, and further preferably 35 to 45°C. The adsorption time is 4 to 24 hours, and may be, for example, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, or 24 hours, more preferably 8 hours to 20 hours, and further preferably 10 hours to 18 hours. After the adsorption, the mixture obtained by the adsorption is suction filtered and washed with one or a combination of two of deionized water, methanol, or ethanol, and the combination may be, for example, deionized water, methanol, ethanol, a combination of deionized water and methanol, a combination of deionized water and ethanol, or a combination of methanol and ethanol. The number of washings is 2 to 5 times, for example, 2 times, 3 times, 4 times, or 5 times, and more preferably 3 to 4 times. The washing time is 0.5 to 24 hours, for example, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 11 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, or 24 hours, and more preferably 5 to 20 hours, and even more preferably 10 to 15 hours. The drying temperature is 60 to 100°C, and may be, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C, more preferably 70 to 90°C, and even more preferably 75 to 85°C. The drying time is 6 to 24 hours, and may be, for example, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours, more preferably 15 to 24 hours, and further preferably 18 to 20 hours.

[0025] Preferably, the roasting in step 4) is carried out in a muffle furnace, a tubular furnace or a kiln; The roasting temperature is 200 to 600°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, or 600°C, more preferably 300 to 550°C, and even more preferably 400 to 500°C. The roasting time is 0.5 to 10 hours, for example, 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, or 10 hours, more preferably 1 hour to 6 hours, and further preferably 2 hours to 4 hours. The heating rate of the roasting may be 0.1 to 20° C. / min, for example, 0.5° C. / min, 1° C. / min, 1.5° C. / min, 2° C. / min, 2.5° C. / min, 3° C. / min, 3.5° C. / min, 4° C. / min, 4.5° C. / min, 5° C. / min, 5.5° C. / min, 6° C. / min, 6.5° C. / min, 7° C. / min, 7.5° C. / min, 8° C. / min, 8.5° C. / min, 9° C. / min, 9.5° C. / min, or 10° C. / min, more preferably 0.5 to 10° C. / min, and even more preferably 1 to 10° C. / min. The atmosphere of the roasting is air or a mixed gas of nitrogen gas and oxygen gas, and the ratio of oxygen gas in the mixed gas of nitrogen gas and oxygen gas is 5-40%, for example, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 25%, 30%, 35%, or 40%. More preferably, the ratio of oxygen gas in the mixed gas of nitrogen gas and oxygen gas is 10-30%, and even more preferably, the ratio of oxygen gas in the mixed gas of nitrogen gas and oxygen gas is 15-25%. The present invention not only adjusts and produces hollow multi-shell hollow spheres by calcination using a mixed atmosphere of nitrogen gas and oxygen gas, but also adjusts the defect content of the multi-shells. The absorption ability of the solar spectrum by the hollow multi-shells is adjusted over a wide range, and the light-to-heat conversion efficiency and water evaporation rate are optimized.

[0026] In the preparation method of the present invention, before roasting, step 1) and step 2) can be repeated 1 to 5 times, thereby obtaining a hollow multi-shell material of amorphous metal oxide having 2 to 4 shell layers.

[0027] The present invention can change the content of different metal oxides in the shell by adjusting the synthesis conditions such as the concentration of two kinds of metal salts with different hydrated ionic radii, the adsorption temperature, the number of repeated adsorptions, and the calcination atmosphere, thereby realizing the efficient absorption of light of different wavelengths by different shells, and further realizing the effect of sequentially absorbing the entire solar spectrum, thereby enhancing the light absorption ability of the photothermal material of the prepared multi-shell hollow sphere, and further improving its photothermal conversion efficiency.

[0028] The present invention provides a hollow multishell material of amorphous metal oxide obtained by the above-mentioned manufacturing method, the hollow multishell material of amorphous metal oxide comprising at least one cavity and at least one shell wall layer, two or more kinds of metal oxides being deposited on the surface of the shell wall, the metal oxide being nanoparticles or nanorods, the metal oxide preferably comprising one or more of tantalum oxide, niobium oxide, hafnium oxide, rhenium oxide, titanium oxide and tungsten oxide, but is not limited thereto.

[0029] The shell wall may have 2 to 4 layers, for example, 2 layers, 3 layers, or 4 layers. The shell wall can sequentially absorb the solar spectrum in multiple stages, and the defect content of the metal oxide deposited on the surface of the outer shell wall of the shell wall is smaller than the defect content of the metal oxide deposited on the surface of the inner shell wall.

[0030] The metal oxide deposited on the surface of the shell wall has defect control properties; It absorbs the ultraviolet, visible, near infrared and mid-infrared portions of the solar spectrum in multiple stages.

[0031] The absorbance of the metal oxide of the shell wall can be adjusted within the range of 10 to 95%.

[0032] The present invention provides a metal oxide material for photothermal water evaporation, the metal oxide material for photothermal water evaporation comprising hollow multi-shell material of the amorphous metal oxide, The metal oxide material for photothermal water evaporation has a power of 100 mW / cm 2 1.6kg / m2 by irradiation with a solar simulator 2 h evaporation rate for efficient surface water evaporation. Effect of the Invention

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] First, the hollow multi-shell composite metal oxide material prepared in the present invention has stronger light absorption ability, and the complex multi-stage structure of the multi-shell can significantly extend the optical path of the incident light inside the material. In addition, the characteristics of the multi-shell itself give the material a larger specific surface area, which makes the material more intimately contact with water. When the hollow sphere is applied to photothermal water evaporation, it can effectively absorb the entire solar spectrum, and the light absorption capacity can reach 100mW / cm2. 2 1.6kg / m2 by irradiation with a solar simulator 2 h, and can achieve efficient surface water evaporation, and a reaction stability of over 48 h, which is much higher than that of nanoparticles of the same composition.

[0035] Second, the present invention uses a two-step enhanced adsorption method to introduce defect-controlled doping energy levels into metal oxide hollow spheres, thereby achieving efficient absorption of each wavelength region in the solar spectrum. [Brief description of the drawings]

[0036] [Figure 1] FIG. 1 is a transmission electron microscope photograph of the amorphous triple-shell Ta2O5 hollow spheres prepared in Example 1 of the present invention. [Diagram 2] FIG. 2 is a transmission electron microscope photograph of the amorphous double-shell Ta2O5 hollow spheres prepared in Example 2 of the present invention. [Diagram 3]FIG. 3 shows the X-ray diffraction patterns of amorphous Ta2O5 hollow spheres in different shells of the present invention. [Figure 4] FIG. 4 shows the UV-Vis absorption spectra of triple-shell Ta2O5 at different calcination temperatures according to the present invention. [Diagram 5] FIG. 5 is the electron paramagnetic resonance spectrum of the amorphous triple-shell Ta2O5 hollow spheres prepared in Example 1 of the present invention. [Figure 6] FIG. 6 is a photothermal water evaporation performance diagram of the multi-shell Ta2O5 hollow sphere prepared in Example 1 of the present invention. [Figure 7] FIG. 7 is a comparison diagram of the concentration before and after the amorphous triple-shell Ta2O5 hollow spheres prepared in Example 1 of the present invention are used in the photothermal evaporation purification of uranium-containing solution. [Figure 8] FIG. 8 is a comparison diagram of the concentration before and after the amorphous triple-shell Ta2O5 hollow spheres prepared in Example 1 of the present invention are used in the photothermal evaporation purification of the pseudovirus SC2-P-containing solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] The present invention will be described in more detail below with reference to specific embodiments.

[0038] The present invention provides a method for producing an amorphous metal oxide hollow multishell material, the method comprising: Step (a) is to add a carbon source aqueous solution having a concentration of 0.1-6M to a reactor at 175-220°C for hydrothermal reaction for 100-180 min, naturally cool, suction filter, and wash 2-5 times, and then dry the product at 60-100°C for 6-24 h to obtain carbon sphere templates; Step (b) dispersing the carbon sphere template obtained in step (a) in a first metal salt solution having a concentration of 0.01 to 0.5 M, the first metal salt solution being one or a combination of at least two of a tantalum chloride solution, a tantalum nitrate solution, a tantalum sulfate solution, a tantalum acetylacetonate solution, a tantalum oxalate solution, and a tantalum ethoxide solution, and heating and adsorbing the first metal salt at 20 to 60°C for 1 to 48 hours, centrifuging the mixture after adsorption, taking out the solid in the lower layer, washing it with deionized water, methanol or ethanol 2 to 5 times, and drying it at 60 to 100°C for 6 to 24 hours to obtain a first solid precursor; Step (c) dispersing the first solid precursor obtained in step (b) in a second metal salt solution having a concentration of 0.5-5M, the second metal salt solution being one or a combination of at least two of a tantalum chloride solution, a tantalum nitrate solution, a tantalum sulfate solution, a tantalum acetylacetonate solution, a tantalum oxalate solution, and a tantalum ethoxide solution, stirring and adsorbing the solution at 20-60°C for 4-24 hours, suction filtering the solution, washing the solution with deionized water, methanol or ethanol 2-5 times, washing the solution for 0.5-24 hours, and drying the solution at 60-100°C for 6-24 hours to obtain a solid precursor; and step (d) of roasting the solid precursor obtained in step (c) in a muffle furnace or a kiln under an atmosphere of air or a mixed gas of oxygen gas and nitrogen gas with an oxygen gas ratio of 5 to 40% for 0.5 to 10 hours at a roasting temperature of 200 to 600°C and a heating rate of 0.1 to 20°C / min, and then cooling to obtain the hollow multi-shell material of the amorphous metal oxide.

[0039] Example 1 1. A method for producing an amorphous metal oxide hollow multishell material, the method comprising the steps of: Step (1): 1.5M sucrose aqueous solution is put into a reactor at 200°C for 135min hydrothermal reaction, naturally cooled, suction filtered, and washed with water three times. The product is placed in a 60°C oven and dried for 24h to obtain a carbon sphere template with a diameter of 2.9μm; Step (2): disperse the carbon sphere template obtained in step (1) in 30 mL of a 0.1 M TaCl5 solution, disperse the carbon spheres uniformly using ultrasonic waves, place them in a beaker, place them in a 30°C water bath for 4 hours of heating and adsorption, centrifuge the mixture after adsorption, take out the solid in the lower layer, wash it with deionized water three times, and dry it in an oven at 60°C for 24 hours to obtain a first solid precursor; Step (3) dispersing the first solid precursor obtained in step (2) in a 0.5M TaCl5 solution, stirring and adsorbing at 40°C for 24 hours, suction filtering, washing with deionized water three times, and drying in an oven at 60°C for 24 hours to obtain a second solid precursor; and step (4). The solid precursor obtained in step (3) is placed in a muffle furnace, heated to 500°C at 0.5°C / min, calcined in a mixed gas of nitrogen gas and oxygen gas, with the oxygen ratio in the mixed gas of nitrogen gas and oxygen gas being 15%, and roasted at a constant temperature for 2 hours, and then naturally cooled to obtain triple shell Ta2O5 hollow spheres, with the shell dimension being about 0.8 μm.

[0040] The transmission electron microscope photograph of the product is shown in FIG. 1, which is an amorphous triple-shell hollow sphere. As shown in FIG. 5, in the electron paramagnetic resonance spectrum of the triple-shell hollow spheres formed at different calcination temperatures, the amorphous multi-shell hollow spheres formed by calcination at 400°C, 500°C, and 600°C show an increase and then decrease in integral area at g=2.002, and an increase and then decrease in defect content. The absorption spectrum results in FIG. 4 conform to the above rule, and the UV-Vis-NIR absorptance reaches a maximum at 500°C. And, as shown in FIG. 6, the 100mW / cm 2 1.6kg / m2 by irradiation with a solar simulator 2h evaporation rate, efficient surface water evaporation can be achieved. Moreover, reaction stability of over 48h can be obtained, which is much higher than that of nanoparticles in the report. Furthermore, the evaporation water source is expanded to uranium-containing radioactive wastewater and pseudovirus (SC2-P)-containing culture medium. The uranium content in the water before and after evaporation is characterized by ICP, and the characterization results are shown in Figure 7. From 200ppm to 8*10 -5 The concentration of uranium was reduced by nearly 6 levels, which is completely in line with the WHO standard. The concentration of SC2-P-containing solution before and after evaporation was amplified and quantified using PCR. The characterization results are shown in Figure 8. 7 The virus concentration is reduced at six levels, from particles / mL to 11.8 particles / mL by evaporation (result after 100-fold concentration of the solution collected after evaporation).

[0041] Example 2 1. A method for producing an amorphous metal oxide hollow multishell material, the method comprising the steps of: Step (1): A 2.5M sucrose aqueous solution is put into a reactor at 180°C for 130 minutes of hydrothermal reaction, naturally cooled, suction filtered, and washed twice with water. The product is placed in an oven at 70°C and dried for 24 hours to obtain a carbon sphere template with a diameter of 2.7 μm; Step (2): dispersing the carbon sphere template obtained in step (1) in 30 mL of 0.2 M tantalum acetylacetonate solution, dispersing the carbon spheres uniformly by ultrasonic waves, placing them in a beaker, placing them in a water bath at 40°C for 3 hours for heating and adsorbing, centrifuging the mixture after adsorption, taking out the solid in the lower layer, washing it three times with deionized water, and drying it in an oven at 60°C for 24 hours to obtain a first solid precursor; Step (3): dispersing the first solid precursor obtained in step (2) in a 1M TaCl5 solution, stirring and adsorbing at 60°C for 12 hours, suction filtering, washing with deionized water three times, and drying in an oven at 70°C for 12 hours to obtain a second solid precursor; and step (4), the second solid precursor obtained in step (3) is placed in a muffle furnace and heated to 600°C at 3°C / min in air, roasted at constant temperature for 1 h, and naturally cooled to obtain triple-shell Ta2O5 hollow spheres, with the shell dimension being about 0.8 μm.

[0042] 100mW / cm 2 1.4kg / m2 by irradiation with a solar simulator 2 h evaporation rate can achieve efficient surface water evaporation.

[0043] Example 3 1. A method for producing an amorphous metal oxide hollow multishell material, the method comprising the steps of: Step (1): 1.5M sucrose aqueous solution is put into a reactor at 195°C for 150min hydrothermal reaction, naturally cooled, suction filtered, and washed with water four times. The product is placed in an oven at 70°C for 18h to obtain a carbon sphere template with a diameter of 2.5μm; Step (2): Disperse the carbon sphere template obtained in step (1) in 30 mL of tantalum oxalate solution with a concentration of 0.2 M, disperse the carbon spheres uniformly using ultrasonic waves, place them in a beaker, place them in a water bath at 20 ° C for 10 h for heating and adsorption, centrifuge the mixture after adsorption, take out the solid in the lower layer, wash it with deionized water three times, and dry it in an oven at 60 ° C for 24 h to obtain a first solid precursor; Step (3) dispersing the first solid precursor obtained in step (2) in a tantalum acetylacetonate solution having a concentration of 1M, stirring and adsorbing the solution at 60°C for 12 hours, suction filtering, washing with deionized water three times, and drying in an oven at 70°C for 12 hours to obtain a second solid precursor; and step (4), the second solid precursor obtained in step (3) is placed in a muffle furnace, heated to 600°C at 16°C / min under an atmosphere of a mixture of nitrogen gas and oxygen gas with an oxygen ratio of 35%, roasted at a constant temperature for 1 h, and naturally cooled to obtain triple-shell Ta2O5 hollow spheres, with the shell dimension being about 0.8 μm.

[0044] 100mW / cm 21.3kg / m2 by irradiation with a solar simulator 2 h evaporation rate can achieve efficient surface water evaporation.

[0045] Example 4 1. A method for producing an amorphous metal oxide hollow multishell material, the method comprising the steps of: Step (1): 5M sucrose aqueous solution is put into a reactor at 200°C for 110 minutes of hydrothermal reaction, naturally cooled, suction filtered, and washed with water three times. The product is placed in an oven at 80°C for 24 hours to obtain a carbon sphere template with a diameter of 2.5 μm; Step (2): disperse the carbon sphere template obtained in step (1) in 30 mL of 0.1 M tantalum ethoxide solution, disperse the carbon spheres uniformly by ultrasonic waves, put them into a beaker, place them in a water bath at 20 ° C for 4 h of heating and adsorption, centrifuge the mixture after adsorption, take out the solid in the lower layer, wash it with deionized water three times, and dry it in an oven at 60 ° C for 24 h to obtain a first solid precursor; Step (3) dispersing the first solid precursor obtained in step (2) in a tantalum pentachloride solution with a concentration of 3M, stirring and adsorbing at 50°C for 12 hours, suction filtering, washing with deionized water three times, and drying in an oven at 70°C for 12 hours to obtain a second solid precursor; and step (4). The second solid precursor obtained in step (3) is placed in a muffle furnace, heated to 400°C at 2°C / min under an atmosphere of a mixture of nitrogen gas and oxygen gas with an oxygen ratio of 40%, roasted at a constant temperature for 1 h, and naturally cooled to obtain triple-shell Ta2O5 hollow spheres, with the shell dimension being about 0.8 μm.

[0046] 100mW / cm 2 1.5kg / m2 by irradiation with a solar simulator 2 h evaporation rate can achieve efficient surface water evaporation.

[0047] Example 5 1. A method for producing an amorphous metal oxide hollow multishell material, the method comprising the steps of: Step (1): 3M sucrose aqueous solution is put into a reactor at 210°C for 130 minutes of hydrothermal reaction, naturally cooled, suction filtered, and washed with water five times. The product is placed in an oven at 90°C for 10 hours to obtain a carbon sphere template with a diameter of 3 μm; Step (2): Disperse the carbon sphere template obtained in step (1) in 30 mL of 0.3 M tantalum sulfate acetone solution, disperse the carbon spheres uniformly using ultrasonic waves, put them into a beaker, place them in a water bath at 50 °C for 4 h for heating and adsorption, centrifuge the mixture after adsorption, take out the solid in the lower layer, wash it with deionized water three times, and dry it in an oven at 60 °C for 24 h to obtain a first solid precursor; Step (3) dispersing the first solid precursor obtained in step (2) in a tantalum pentachloride solution with a concentration of 3M, stirring and adsorbing at 50°C for 12 hours, suction filtering, washing with deionized water three times, and drying in an oven at 70°C for 12 hours to obtain a second solid precursor; and step (4). The second solid precursor obtained in step (3) is placed in a muffle furnace, heated to 250°C at 5°C / min under an atmosphere of a mixture of nitrogen gas and oxygen gas with an oxygen ratio of 30%, and roasted at a constant temperature for 1 h, and then naturally cooled to obtain triple-shell Ta2O5 hollow spheres, with the shell dimension being about 1 μm.

[0048] 100mW / cm 2 1.2kg / m2 by irradiation with a solar simulator 2 h evaporation rate can achieve efficient surface water evaporation.

[0049] Example 6 1. A method for producing an amorphous metal oxide hollow multishell material, the method comprising the steps of: Step (1): 2M sucrose aqueous solution is put into a reactor at 200°C for 160min hydrothermal reaction, naturally cooled, suction filtered, and washed with water three times. The product is placed in an oven at 60°C and dried for 24h to obtain a carbon sphere template with a diameter of 2.8μm; Step (2): Disperse the carbon sphere template obtained in step (1) in 30 mL of 0.5 M tantalum pentachloride acetone solution, disperse the carbon spheres uniformly using ultrasonic waves, put them into a beaker, place them in a water bath at 30 °C for 12 h of heating and adsorption, centrifuge the mixture after adsorption, take out the solid in the lower layer, wash it with deionized water three times, and dry it in an oven at 60 °C for 24 h to obtain a first solid precursor; Step (3): dispersing the first solid precursor obtained in step (2) in a tantalum pentachloride acetone solution with a concentration of 4M, stirring and adsorbing at 40°C for 24 hours, suction filtering, washing with deionized water three times, and drying in an oven at 70°C for 12 hours to obtain a second solid precursor; and step (4). The second solid precursor obtained in step (3) is placed in a muffle furnace, heated to 550°C at 10°C / min under an atmosphere of a mixture of nitrogen gas and oxygen gas with an oxygen ratio of 10%, roasted at a constant temperature for 1 h, and naturally cooled to obtain triple-shell Ta2O5 hollow spheres, with the shell dimension being about 1 μm.

[0050] Any content not described in detail in the present invention may be understood by those skilled in the art.

[0051] Finally, it should be explained that the above embodiments are merely for illustrating the technical solution of the present invention, and are not intended to be limiting. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art will understand that any modification or equivalent replacement made to the technical solution of the present invention will not depart from the spirit and scope of the technical solution of the present invention, and all of them should be included in the scope of the claims of the present invention.

Claims

1. 1. A method for producing an amorphous metal oxide hollow multishell material, comprising the steps of: Step 1) heating and reacting an aqueous carbon source solution, and obtaining carbon sphere templates through filtration, washing and drying; Step 2) dispersing the carbon sphere template obtained in step 1) in a first metal salt solution, heating and adsorbing the salt, and drying the salt in an oven to obtain a first solid precursor; Step 3) dispersing the solid precursor obtained in step 2) in a second metal salt solution again, adsorbing and oven drying to obtain a second solid precursor; and step 4) roasting the second solid precursor obtained in step 3) to obtain an amorphous metal oxide hollow multishell material, The first metal salt solution and the second metal salt solution in step 2) and step 3) each include one or more of a tantalum chloride solution, a tantalum nitrate solution, a tantalum sulfate solution, a tantalum acetylacetonate solution, a tantalum oxalate solution, and a tantalum ethoxide solution; a concentration of hydrated ions in the second metal salt solution is equal to or greater than a concentration of hydrated ions in the first metal salt solution; A method for producing a hollow multishell material of an amorphous metal oxide, characterized in that a solvent of the first metal salt solution comprises one or more of water, acetone and ethanol, and a solvent of the second metal salt solution comprises water and / or ethanol.

2. 2. The method according to claim 1, wherein the carbon source in step 1) comprises one or more of glucose, fructose, sucrose, maltose, starch, and citric acid, and the concentration of the carbon source in the aqueous carbon source solution is 0.1 to 6 M.

3. The method according to claim 1, wherein the heating reaction in step 1) is a hydrothermal reaction, the hydrothermal reaction is carried out in a reaction vessel, the hydrothermal reaction temperature is 175-220°C, the hydrothermal reaction time is 100-180min, the drying temperature is 60-100°C, and the drying time is 6-24h.

4. The method of claim 1, wherein the concentration of the first metal salt solution is 0.01 to 0.5M, and the concentration of the second metal salt solution is 0.5 to 5M.

5. 2. The method according to claim 1, wherein the solvent of the first metal salt solution comprises acetone and / or ethanol, and the solvent of the second metal salt solution is water.

6. In the step 2), the adsorption temperature is 20 to 60° C., the adsorption time is 1 to 48 h, the drying temperature is 60 to 100° C., and the drying time is 6 to 24 h; 2. The method according to claim 1, wherein in step 3), the adsorption temperature is 20 to 60° C., the adsorption time is 4 to 24 h, the drying temperature is 60 to 100° C., and the drying time is 6 to 24 h.

7. The roasting in step 4) is carried out in a muffle furnace, a tubular furnace or a kiln; The roasting temperature is 200 to 600°C, the roasting time is 0.5 to 10 h, and the roasting temperature increase rate is 0.1 to 20°C / min; 2. The method according to claim 1, wherein the roasting atmosphere is air or a mixed gas of nitrogen gas and oxygen gas, and a ratio of oxygen gas in the mixed gas of nitrogen gas and oxygen gas is 5 to 40%.

8. 1. A hollow multi-shell material of amorphous metal oxide, comprising at least one cavity and at least one shell wall, wherein two or more metal oxides are deposited on a surface of said shell wall, said metal oxides being nanoparticles or nanorods, said metal oxides comprising one or more of tantalum oxide, niobium oxide, hafnium oxide, rhenium oxide, titanium oxide and tungsten oxide; The shell wall has 2 to 4 layers, and the shell wall can sequentially absorb the solar spectrum in multiple stages; It absorbs the ultraviolet, visible, near-infrared and mid-infrared light portions of the solar spectrum in multiple stages, 1. A hollow multi-shell material of amorphous metal oxide, characterized in that the absorbance of the metal oxide of the shell walls is within 10-95%.

9. 1. A metal oxide material for photothermal water evaporation comprising:

10. A metal oxide material for photothermal water evaporation comprising the amorphous metal oxide hollow multi-shell material of claim 8.

Citation Information

Patent Citations

  • Metallic oxide / metal sulfide hollow nanospheres as well as preparation method and application thereof

    CN104492460A

  • Multi-shell metal oxide hollow sphere synthesized based on anion adsorption and preparation method as well as application thereof

    CN105762349A

  • Composite metal oxide hollow multi-shell material and preparation method and application thereof

    CN109876809A

  • Core / shell structure and hollow shell structure and method for producing those

    JP2008111058A

  • Ceria-based composite hollow microparticle dispersion, production method thereof, and polishing abrasive grain dispersion comprising ceria-based composite hollow microparticle dispersion

    JP2019127405A